Integrating Village Digitalization and Health Interventions: Inclusive Transformation in Paddinging Village, South Sulawesi - Eljihad Akbari Syukriah Mathory; Juniarto Matasak; NabilaRhamadani Rhamadani; Sumayyah HR; Dava Fudail Pontoh (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to address the digital technology gap and the high prevalence of stunting in Paddinging Village, South Sulawesi, through an integrated community service program combining village digitalization and public health intervention. The significance of this initiative lies in its potential to serve as a replicable model for inclusive and sustainable village development, particularly in underdeveloped, frontier, and outermost (3T) areas across Indonesia. A qualitative participatory approach was employed, utilizing observation, semi-structured interviews, training, direct demonstrations, and active coordination with village officials, local youth, Posyandu cadres, and community members. Three main programs were implemented: (1) the creation of a Google Sites-based village website to enhance public information transparency and service accessibility; (2) QRASPIRASI, a QR code-based digital suggestion box system using Google Forms to strengthen citizen participation and government responsiveness; and (3) a stunting prevention intervention through nutrition education, toddler growth monitoring, and healthy food cooking demonstrations in collaboration with Posyandu cadres and Puskesmas health workers. The key findings demonstrate that the village website successfully improved access to public information and governance transparency, QRASPIRASI effectively facilitated two-way communication between residents and the village government with faster documented responses, and the stunting program enhanced parental knowledge of balanced nutrition and early detection of at-risk toddlers. These findings imply that an integrative model combining digital transformation and community health intervention is effective in promoting participatory, transparent, and sustainable village development, and can be adapted for other regions facing similar challenges in alignment with the Sustainable Development Goals and the national village digitalization agenda.